Dissociation of subjective and objective measures of trust in vehicle automation: a driving simulator study - Petkac, Samuel; Sato, Tetsuya; Xie, Kun; Yamani, Yusuke (Frontiers in Future Transportation, 2025)
Trust is a crucial factor that influences human-automation interaction in surface transportation. Previous research indicates that participants tend to display higher levels of subjective trust toward lower-level automated systems compared to high-level automated systems. However, administering subjective trust measures via questionnaires can interfere with primary task performance, limiting researchers’ ability to measure trust continuously in a real-world manner. The current study investigated whether objective and subjective measures of trust exhibit similar patterns across different levels of automation in a simulated driving environment. Twenty-five drivers using an automated driving system (ADS) were randomly assigned to either an active (L2) or passive (L3) automated driving condition. Participants experienced eight near-miss driving scenarios with or without obstructions in a distributed driving simulator and rated their subjective trust before and after navigating the scenarios. Additionally, we coded hand positions from recorded video footage of the participants’ in-vehicle behavior. Hand placements were coded on a predefined five-point system near the time of the simulated connected vehicle technology’s collision alert. Results showed that drivers progressively lost trust in the automated system as they approached and passed the projected collision point in each scenario. Furthermore, drivers in the active condition displayed lower levels of trust than those in the passive condition. This finding contrasts with previous research suggesting that subjective trust ratings are comparable between Level 2 and Level 3 vehicle automation groups. These findings highlight a dissociation between subjective and behavioral measures of trust, suggesting that self-report methods may overlook important aspects of drivers’ trust that can be captured through behavioral measures.